Adolescent reports of subjective socioeconomic status: An adequate alternative to parent-reported objective and subjective socioeconomic status? - Erin K Davisson; Fernanda C Andrade; Jennifer Godwin; Rick Hoyle (PLoS ONE)
Socioeconomic status (SES) is associated with well-being outcomes across studies; however, there is wide variation in its measurement, particularly in adolescence. One key difference in measures of SES concerns whether participants relay objective information-for example, years of education, household income-or subjective perceptions of socioeconomic status, either with or without reference to others or society. Although parents are often considered the best source of SES information-especially objective SES-within families, interviewing parents within the context of adolescent research is costly, time-consuming, and not always feasible. Given the importance of SES for outcomes in adolescence and cumulative effects over the lifespan, we used data from adolescents (N = 702) and parents (Ns = 664-730) to examine whether adolescent reports of SES serve as reasonable proxies for parent reports of both objective and subjective SES, as well as administrative data assessing family SES and neighborhood SES. Consistent with our hypotheses, adolescents' reports of subjective SES were moderately correlated with parent reports and administrative data tapping family SES. Moreover, adolescents' reports of subjective SES predicted adolescent-reported measures of well-being, including mental health, physical health, school performance, problem behavior, and alcohol use to the same degree as or better than parent reports of both subjective and objective SES and administrative data. These findings suggest that adolescent reports of subjective SES-using two different, easily understood measures-can stand in as reasonable alternatives to parent-reported SES and administrative data.